WHAT ARE THE MNC'S IMPACTS ON CSR AND LABOUR ISSUES IN CHINA - Shen, Yating (2006)
It can be assumed that the globalisation stimulated and encouraged the emergence of CSR, and it is a function of economic and social development. (Chapple and Moon, 2005) Labour issues are not purely about the human resource concerns, but also deeply rooted into the global development issues. (Hopkins, 2003) With the trend that MNCs greatly invested in Chinese market, they also brought the concept of CSR into the Chinese society. (Corp Watch, 2005) This study will present an investigative primary research on the impacts of MNCs on CSR and labour issues in China. Also, the analysis will focus on the culture, tradition, and ethical aspects which link to various stakeholders' point of view on the topic.